ANALISIS KOORDINASI PETUGAS APRON MOVEMENT CONTROL (AMC) DALAM PENEMPATAN PARKING STAND PESAWAT DI BANDAR UDARA INTERNASIONAL YOGYAKARTA - Rizki Putra Pamungkas (CV. ADIBA AISHA AMIRA, 2025)
The placement of the parking stand is the responsibility of the Apron Movement Control unit to ensure accuracy and order. This unit is required to cooperate with other relevant units. The purpose of this study is to identify how AMC officers coordinate when determining aircraft parking spaces, as well as the constraints and efforts made. This study uses a qualitative method that collects data through observation, interviews, and documentation. The data collected by the study were analyzed, reduced, and a conclusion was drawn from the results of the study. The AMC unit has complied with the Standard Operating Procedures that have been established in the placement of the parking stand. One of the obstacles in this case is a miscommunication that results in data input errors regarding parking stands and inconsistencies with gates. In addition, technical obstacles in the placement of parking stands such as cracks in the parking stand, oil spills in the parking stand area, and damage to the aviobridge. The efforts made are to improve communication between units and conduct regular briefings and evaluations.